Nanotechnologies for synthetic super non-wetting surfaces - Senez, Vincent (FOCUS Series., 2014)
Texturing surfaces at micro- and/or nano-scales modifies the interactions of liquids and solids. This book is a summary of the state of the art concerning the development and use of micro/nano-technologies for the design of synthetic liquid repellent surfaces with a particular focus on super-omniphobic materials. It proposes a comprehensive understanding of the physical mechanisms involved in the wetting of these surfaces and reviews emerging applications in various fields such as energy harvesting and biology, as well as highlighting the current limitations and challenges which are yet to be.